Recent advances in high‐loading catalysts for low‐temperature fuel cells: From nanoparticle to single atom. Issue 4 (31st December 2021) - Shen, Lixiao; Ma, Miao; Tu, Fengdi; Zhao, Zigang; Xia, Yunfei; Goh, Kokswee; Zhao, Lei; Wang, Zhenbo; Shao, Guangjie
Abstract: Low‐temperature fuel cells (LTFCs) are considered to be one of the most promising power sources for widespread application in sustainable and renewable energy conversion technologies. Although remarkable advances have been made in the mass activity of catalysts, mass transport impedance needs to be urgently addressed at a well‐designed membrane electrode assembly (MEA) scale. Increasing the loading of electrocatalysts is conducive to prepare thinner and more efficient MEAs owing to the resulting enhanced reactant permeability, better proton diffusion, and lower electrical resistance. Herein, recent progress in high‐loading (≥40 wt.%) Pt nanoparticle catalysts (NPCs) and high‐loading (≥2 wt.%) single‐atom catalysts (SACs) for LTFC applications are reviewed. A summary of various synthetic approaches and support materials for high‐loading Pt NPCs and SACs is systematically presented. The influences of high surface area and appropriate surface functionalization for Pt NPCs, as well as coordination environment, spatial confinement effect, and strong metal‐support interactions (SMSI) for SACs are highlighted. Additionally, this review presents some ideas regarding challenges and future opportunities of high‐loading catalysts in the application of LTFCs. Abstract : Increasing the loading of electrocatalysts is considered as a practical strategy to achieve thin catalyst layer resulting in smooth reactant permeability and low electrical resistance. Various synthetic approaches and functionalized support materials are presented for obtaining high‐loading Pt nanoparticle catalysts (≥40 wt.%) and single‐atom catalysts (≥2 wt.%).